Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

Distribution and migration phenology of Purple Martins (Progne subis) in Brazil - Clarissa O. Santos; Jonathan M. Branco; Maria C. T. D. Belotti; Pedro Abilleira; Joe Siegrist; Jason Fischer; Luciano M. Lima; Mario Cohn-Haft; Erika Hingst-Zaher (Ornithology Research, 2021)

Video Education on Hereditary Breast and Ovarian Cancer (HBOC) for Physicians: an Interventional Study - Bhuma Krishnamachari; Mahin Rehman; Jason E. Cohn; Vivian Chan; Neil Modi; Ofri Leitner; Kelly Tangney; April O’Connor; William Blazey; Sharon Koehler; David Tegay (Journal of Cancer Education, 2018)

Physician Risk Assessment Knowledge Regarding BRCA Genetics Testing - Jason Cohn; William Blazey; David Tegay; Brian Harper; Sharon Koehler; Brookshield Laurent; Vivian Chan; Min-Kyung Jung; Bhuma Krishnamachari (Journal of Cancer Education, 2015)